# Math

posted by .

Is 2Cos x the same thing as Cos^2 x?
Thanks

• Math -

No it is not.

## Similar Questions

1. ### Trig.......

I need to prove that the following is true. Thanks (2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx) and thanks ........... check your typing. I tried 30ยบ, the two sides are not equal, they differ by 1 oh , thank you Mr Reiny …
2. ### Trigonometry

Need help solving problems using the Trigonometric Identities: 8cos^4 thet=cos4theta+4cos2theta+3 I am a bit unsure how to solve it. I am aware that the first step I must take is to simplify the problem and then use the Product to …
3. ### math

cosA= 5/9 find cos1/2A are you familiar with the half-angle formulas?
4. ### Math - Trig - Double Angles

Prove: cos4x = 8cos^4x - 8cos^2x + 1 My Attempt: RS: = 4cos^2x (2cos^2x - 1) + 1 = 4 cos^2x (cos2x) + 1 LS: = cos2(2x) = 2cos^2(2x) - 1 = (cos^2(2)) - cos^2(2x)) - 1 ----- Prove: 8cos^4x = cos4x + 4cos2x + 3 My Attempt: RS: = cos2(2x) …
5. ### Math - Solving for Trig Equations

Solve the following equation for 0 less than and/or equal to "x" less than and/or equal to 360 -- cos^2x - 1 = sin^2x -- Attempt: cos^2x - 1 - sin^2x = 0 cos^2x - 1 - (1 - cos^2x) = 0 cos^2x - 1 - 1 + cos^2x = 0 2cos^2x - 2 = 0 (2cos^2x/2)= …
6. ### Math - Solving Trig Equations

What am I doing wrong? Equation: sin2x = 2cos2x Answers: 90 and 270 .... My Work: 2sin(x)cos(x) = 2cos(2x) sin(x) cos(x) = cos(2x) sin(x) cos(x) = 2cos^2(x) - 1 cos(x) (+/-)\sqrt{1 - cos^2(x)} = 2cos^2(x) - 1 cos^2(x)(1 - cos^2(x))
7. ### Pre-Cal

verify the identity sin x(1 - 2 cos^2 x + cos^4 x) = sin^5 x 1-2cos^2 x looks like 2cos^2x-1 its just backwards. I am not sure where to start.
8. ### trig

I don't understand this. can you please tell how you got each answer?
9. ### Calculus

which of the following integrals results from making the substitution u=x^3 in orer to find (squiggly vertical line)x^2cos(x^3)dx ~cos u du ~u^2 cos u du ~u^(2/3) cos u du1/3 os u du ~3 cos u du
10. ### Maths

y = -14sin(8x)2cos(5x) - 4sin(5x)cos(8x) u = -14sin(8x) u' = -112cos(8x) v = 2cos(5x) v' = -10sin(5x) u2 = -4sin(5x) u'2 = -20cos(5x) v2 = cos(8x) v'2 = -8sin(8x) y' = (uv') + (vu') + (u2v'2) + (v2u'2) y' = [(-14sin(8x))(-10sin(5x)] …

More Similar Questions